Leptin ameliorates burn-induced multiple organ damage and modulates postburn immune response in rats - YEGEN, BERRAK; ERCAN, FERİHA (ELSEVIER, 2005)
The present study was designed to determine whether exogenous leptin reduces remote organ injury in the rats with thermal burn trauma. Leptin (10 mug/kg) or saline was administered intraperitoneally after burn injury, and the rats were decapitated at either 6 or 24 h. Plasma samples of 24-h burn group were assayed for the determination of monocyte and neutrophil apoptosis. Thermal injury increased tissue-associated myeloperoxidase (MPO) activity and microscopic damage scores in the lung, liver, stomach, colon and kidney of both 6- and 24-h burn groups. In the 6-h burn group, leptin reduced microscopic damage score in the liver and kidney only, while damage scores in the 24-h burn group were reduced in all the tissues except the lung. Also, in both burn groups, leptin reduced elevated MPO activity in all tissues except the lung. The percentage of mononuclear cells was significantly reduced at the 24 h of burn injury, while the granulocyte percentage was increased. Leptin treatment, however, had no significant effect on burn-induced reversal of white blood cell ratios. On the other hand, burn-induced increase in the death of mononuclear cells and granulocytes was significantly reduced in leptin-treated rats. The results of the present study suggest that leptin may provide a therapeutic benefit in diminishing burn-induced inflammation and associated multiple organ failure. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: burn injury; multiple organ damage; myeloperoxidase; immunosuppression; NECROSIS-FACTOR-ALPHA; PLASMA LEPTIN; INFLAMMATION; EXPRESSION; CYTOKINES; SURVIVAL; RECEPTOR; MYELOPEROXIDASE; CHOLECYSTOKININ; REGULATOR